Shape and size analysis of calcium alginate particles produced through extrusion method - Lee, Boon Beng (2008)
Alginate is the most widely used biopolymer for bioencapsulation because it can form thermally stable and biocompatible gel particles in the presence of calcium cation by using simple extrusion method. Particles which are spherical in shape and uniform in size are highly desirable in many applications. Formation of particles with these characteristics is influenced by a combination of process variables such as solution properties and operation conditions. The primary objective of this work is to study the inter-relationship of process variables on shape and size of calcium-alginate particles produced through extrusion-dripping method given that no such systematic study has been reported in the past. The first part of this research involved measurement of alginate solutions density, viscosity and surface tension. The second part involved shape and size analysis of travelling Na-alginate solution droplets and calcium-alginate particles produced under various process conditions. Dimensionless number groups were used to develop the inter-relationships between the process variables. The final part involved development of a mathematical model for prediction of particle size. In this research, it was found that the surface tension decreased as the concentration of alginate solution increased. Conversely, the density and viscosity of alginate solution increased as the concentration of alginate solution increased. For shape analysis, the spherity of calcium-alginate particle was found to be affected by the combined influence of the solution properties, the collecting distance and the droplet size. Spherical particle could only be formed when OhI > 0.25. Furthermore, the shape of Ca-alginate particles could be typically distinguished into three phases along the collecting distance. The transition points of the distance between the phases can be described by a shape diagram which is a plot of the impact Reynolds number (ReI) and the impact Ohnesorge number (OhI) of the Na-alginate solution drops at the point of liquid-liquid impact. The diagram also reveals a clear operating region and the process limits within which spherical Ca-alginate particles could be formed. In term of particle size, an overall size reduction factor (K) was introduced to modify the size predicted from Tate’s law by taking into account the Na-alginate solution droplet correction factor (kHB) and shrinkage factor (kS). The Na-alginate solution droplet correction factor (kHB) was independent of the Na-alginate solution physical properties but was dependent on the tip size. It could be described by a quadratic equation within the experimental limits. The shrinkage factor (ks) was found to be affected by the M/G ratio of alginate. The size reduction factor (K) varied from 0.73-0.85 under the experimental conditions and the size prediction model was found to correlate well with the experimental data with an average absolute deviation of less than 5%. In short, the shape diagram and prediction models can be used to produce spherical Ca-alginate particles with desirabed size.